Environment-Specific Probiotic Supernatants Modify the Metabolic Activity and Survival of Streptococcus mutans in vitro - Yu, Haiyue; Ganas, Petra; Schwendicke, Falk (Frontiers in Microbiology, 2020)
A range of studies showed probiotics like Streptococcus oligofermentans and Limosilactobacillus reuteri to inhibit the cariogenic activity and survival of Streptococcus mutans, possibly via the production of substances like H2O2, reuterin, ammonia and organic acids. We aimed to assess the environment-specific mechanisms underlying this inhibition. We cultured L. reuteri and S. oligofermentans in various environments; minimal medium (MM), MM containing glucose (MM+Glu), glycerol (MM+Gly), lactic acid (MM+Lac), arginine (MM+Arg) and all four substances (MM+all) in vitro. Culture supernatants were obtained and metabolite concentrations (reuterin, ammonia, H2O2, lactate) measured. S. mutans was similarly cultivated in the above six different MM variation media, with glucose being additionally added to the MM+Gly, MM+Lac, and MM+Arg group, with (test groups) and without (control groups) the addition of the supernatants of the described probiotic cultures. Lactate production by S. mutans was measured and its survival (as colony-forming-units/mL) assessed. L. reuteri environment-specifically produced reuterin, H2O2, ammonia and lactate, as did S. oligofermentans. When cultured in S. oligofermentans supernatants, lactate production by S. mutans was significantly reduced (p<0.01), especially in MM+Lac+Glu and MM+all, with no detectable lactate production at all (controls means±SD: 4.46±0.41mM and 6.00±0.29 mM, respectively, p<0.001). A similar reduction in lactate production was found when S. mutans was cultured in L. reuteri supernatants (p<0.05) for all groups except MM+Lac+Glu. Survival of S. mutans cultured in S. oligofermentans supernatants in MM+Lac+Glu and MM+all was significantly reduced by 0.6-log10 and 0.5-log10, respectively. Treatment with the supernatant of L. reuteri resulted in a reduction in the viability of S. mutans in MM+Gly+Glu and MM+all by 6.1-log10 and 7.1-log10, respectively. Probiotic effects on the metabolic activity and survival of S. mutans were environment-specific through different pathways.